Cardiac Mechano-Gated Ion Channels and Arrhythmias. Issue 2 (22nd January 2016) - Peyronnet, Rémi; Nerbonne, Jeanne M.; Kohl, Peter
Abstract : Mechanical forces will have been omnipresent since the origin of life, and living organisms have evolved mechanisms to sense, interpret, and respond to mechanical stimuli. The cardiovascular system in general, and the heart in particular, is exposed to constantly changing mechanical signals, including stretch, compression, bending, and shear. The heart adjusts its performance to the mechanical environment, modifying electrical, mechanical, metabolic, and structural properties over a range of time scales. Many of the underlying regulatory processes are encoded intracardially and are, thus, maintained even in heart transplant recipients. Although mechanosensitivity of heart rhythm has been described in the medical literature for over a century, its molecular mechanisms are incompletely understood. Thanks to modern biophysical and molecular technologies, the roles of mechanical forces in cardiac biology are being explored in more detail, and detailed mechanisms of mechanotransduction have started to emerge. Mechano-gated ion channels are cardiac mechanoreceptors. They give rise to mechano-electric feedback, thought to contribute to normal function, disease development, and, potentially, therapeutic interventions. In this review, we focus on acute mechanical effects on cardiac electrophysiology, explore molecular candidates underlying observed responses, and discuss their pharmaceutical regulation. From this, we identify open research questions and highlight emerging technologies that may help in addressing them.